Regional Differences in Outcomes of Nonvariceal upper Gastrointestinal Bleeding in Saskatchewan. Issue 3 (2014) - O'Byrne, Michael; Smith-Windsor, Erin L; Kenyon, Chris R; Bhasin, Sanchit; Jones, Jennifer L
Abstract : BACKGROUND: Nonvariceal upper gastrointestinal bleeding (NVUGIB) is associated with significant mortality. OBJECTIVE: To examine several factors that may impact the mortality and 30-day rebleed rates of patients presenting with NVUGIB. METHODS: A retrospective study of the charts of patients admitted to hospital in either the Saskatoon Health Region (SHR) or Regina Qu'Appelle Health Region (RQHR) (Saskatchewan) in 2008 and 2009 was performed. Mortality and 30-day rebleed end points were stratified according to age, sex, day of admission, patient status, health region, specialty of the endoscopist and time to endoscopy. Logistic regression modelling was performed, controlling for the Charlson comorbidity index, age and sex as covariates. RESULTS: The overall mortality rate observed was 12.2% (n=44), while the overall 30-day rebleed rate was 20.3% (n=80). Inpatient status at the time of the rebleeding event was associated with a significantly increased risk of both mortality and rebleed, while having endoscopy performed in the RQHR versus SHR was associated with a significantly decreased risk of rebleed. A larger proportion of endoscopies were performed both within 24 h and by a gastroenterologist in the RQHR. CONCLUSION: Saskatchewan has relatively high rates of mortality and 30-day rebleeding among patients with NVUGIB compared with published rates. The improved outcomes observed in the RQHR, when compared with the SHR, may be related to the employ of a formal call-back endoscopy team for the treatment of NVUGIB.